Evaluation of Indonesia's Energy Policy Implementation in the Oil Sector to Strengthen National Defense - Rizaldi, Bobby Adhityo; Perwita, Anak Agung Banyu; Widjayanto, Joni; Madjid, M. Adnan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Russia's invasion of Ukraine has resulted in an increase in world crude oil prices, causing an energy crisis in many countries. The crisis lifted food, goods, transportation, and other commodities’ prices. Indonesia is one of the countries affected by the increase in world crude oil prices as the country is still dependent on imported oil. Energy policies that have been issued by the Indonesian government must be able to overcome the energy crisis that is currently occurring in Indonesia. The policies issued by the government have not been able to overcome the energy vulnerability that has occurred in Indonesia, so the government needs to rethink its energy policy to protect the country from the energy crisis. This study focuses on evaluating policies in the Indonesian petroleum sector. The objective of this research is to determine whether the policies implemented by the government align with current global environmental changes. The study was conducted using qualitative research methods through a literature review approach which was carried out by collecting data and information related to the policy of increasing world crude oil prices that occurred domestically and abroad. The research shows that the energy security policy in Indonesia needs to be strengthened and clarified, as this is closely related to the development of Indonesia's defense to become a strong and self-reliant nation.